Biomechanical Effects of Dominant or Nondominant Limb on Asymmetry during Running Stance Phase - Xinci You; Yang Song; Zhuqing Mao; Julien S. Baker; Yaodong Gu (Applied Bionics and Biomechanics)
Purpose. This study explores lower limb joint displacement differences during the stance phase and to examine the effects of limb dominance on asymmetry. A total of 32 healthy male amateur marathon runners were recruited (age: 35.33 ± 6.90 years, height: 174.17 ± 3.34 cm, weight: 63.92 ± 4.53 kg). The experiment employed a Vicon eight-camera motion capture system synchronized with an AMTI force plate to record the phase from heel strike to toe-off. The continuous relative phase (CRP) between the dominant and nondominant limbs was assessed using of independent t-test of SPM1d. Results. The hip–knee joint of the dominant limb had a larger maximum CRP (t = 1.104, p >0.05, effect size = 0.270), smaller minimum CRP (t = −2.672, p <0.05, effect size = 0.653), larger values of mean absolute relative phase (MARF) (t = 3.275, p <0.05, effect size = 0.122), and deviation phase (DP) (t = 7.582, p <0.001, effect size = 0.717) than that of the nondominant limb. Comparing the dominant limb of the knee–ankle joints with the nondominant, there are smaller maximum CRP (t = −0.422, p >0.05, effect size = 0.144), smaller DP (t = −7.237, p <0.001, effect size = 0.754), a larger minimum CRP (t = 7.909, p <0.001, effect size = 2.704), and larger MARF (t = 0.355, p >0.05, effect size = 0.801). Furthermore, during the stance phases, there are significant differences in coordination modes between the dominant limb and nondominant limb of intersegmental joints (p <0.05). Conclusion. Throughout different phases of the stance phase, asymmetry in the sagittal plane of lower limb joint displacement is evident. The dominant limb undergoes significant changes in joint leading phase coordination modes, with notably less in-phase coordination compared to the nondominant limb. This predisposes muscles to overstretching, thereby increasing the risk of muscle strains, while the nondominant limb compensates for lower muscle strength. Recognizing and addressing such asymmetries is key to optimizing nondominant limb strength and minimizing muscle overstretching in the dominant limb, leading to improved stability and movement efficiency during marathon running. Consequently, when designing exercise programs or physical therapy, it is crucial to consider limb dominance-related symmetry differences to mitigate the risk of injury resulting from interlimb disparities in motion.